2020
DOI: 10.3390/su12135226
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Management as a Tool for Sustainable Development of Health Care Facilities

Abstract: Organizations providing health services are often criticized because of inadequate and unsuitable management processes or procedures. Today’s challenge is focused on effective management and leadership skills in the area of health care. The aim of the research is to describe, analyze, and evaluate the current state of diversity management in details in the context of human resources management in the selected healthcare facilities. The source of the information was a questionnaire survey. The sample consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…When employees get the opportunity to craft their roles and jobs they can perform better and could find improved and innovative ways for accomplishing their tasks. The findings of this study also supports the argument outlined in diversity literature of health sector and the premise of this study, that an hospital, which manages diversity well and is perceived by their workers as fair to all parts of the workforce, will experience positive outcomes ( Jankelová et al, 2020 ). In health industry it was experienced that nurses who perceived better diversity climate are more innovative ( Gomez & Bernet, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…When employees get the opportunity to craft their roles and jobs they can perform better and could find improved and innovative ways for accomplishing their tasks. The findings of this study also supports the argument outlined in diversity literature of health sector and the premise of this study, that an hospital, which manages diversity well and is perceived by their workers as fair to all parts of the workforce, will experience positive outcomes ( Jankelová et al, 2020 ). In health industry it was experienced that nurses who perceived better diversity climate are more innovative ( Gomez & Bernet, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…Aggravated by the global spread of COVID-19, cross-cultural conflicts such as trade barriers, ultra-nationalism, and regional discrimination have increasingly intensified worldwide, highlighting the challenges faced in a multicultural organizational environment [ 1 , 2 ]. At the same time, the global flow of human resources and the influx of a large number of "new generation employees" have led to employee differentiation, resulting the "personalized" development of corporate culture [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, no study was found in which all three variables were used together. However, it is frequently emphasized in the literature that organizations should encourage differences rather than ignore them, value the workforce from different backgrounds, and try to improve their ability to manage them, in order to gain a sustainable competitive advantage in differentiated markets ( McCann and Kohntopp, 2017 ; Rahman, 2019 ; Jankelová et al, 2020 ). Therefore, when we look at the issue from the point of view of educational organizations, having a strong sustainable leadership structure of the organization for a sustainable success will be the key to the successful management of the diversities within the institution.…”
Section: Resultsmentioning
confidence: 99%